MAKNA LABA DALAM SUDUT PANDANG PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Setyowati, Ani (Solusi, 2022)
Profit can be assumed as an important component to describe the positif financial condition in a business. Based on this basis, the achievement of the profit statement is something that is often pursued by business. Even to pursue a condition called profit, an organization's management often uses various ways to pursue the profit position. In the other side, profit can be assumed as an excess of the difference between all receipts and all expenditures. But, in the different opinion, profit also increasingly in meaning along with the perception by Micro, Small and Medium Enterprises (MSMEs). Based on the capability  and len s indicators obtained by the MSME actors. The purpose of this study is to explore the meaning of profit from the perspective actors of MSMEs. The research method uses a phenomenological approach. Then the results of the analysis were obtained by digging up information at the research site through interviews with three MSME actors. The research shows the results that MSME actors describe profits based on various perspectives such as the ability of MSME owners to complete obligations related to employee salary costs, electricity costs, and can run operations even though economic conditions are not stable.